OP0237 Twist1 Amplifies Canonical Tgf-Beta Signaling in Ssc. (10th June 2014) - Palumbo-Zerr, K.; Liebl, A.; Zerr, P.; Distler, A.; Beyer, C.; Distler, O.; Schett, G.; Distler, J.H.
Abstract : Background: Twist1 is a member of the tissue-restricted class B of basic-helix-loop-helix (bHLH) transcription factors acting as regulators on different tissues. Twist1 activation is controlled by spatial-temporal expression, dimer choice and subcellular localization. Twist1 has been shown to be a regulator of epithelial mesenchymal transition (EMT). Twist1 signaling is known to be modified by other classes of bHLH transcription factors such as ubiquitously expressed E proteins and inhibitory Id proteins. However, its role for the activation of resident fibroblasts and pathogenesis of non-epithelial organs has yet not been investigated. Objectives: The aim of the present study was to investigate the role of Twist1 in TGFβ signaling and in the pathogenesis of systemic sclerosis (SSc). Methods: Twist signaling was modulated by siRNA or overexpression constructs. Interaction of Twist1, E12 and Ids was shown by co-immunoprecipitation (Co-IP). Chromatin immunoprecipitation (ChIP) assays were performed to analyze Twist1transcriptional binding. The role of Twist1 in vivo was evaluated using mice with ubiquitous or fibroblast-specific depletion of Twist1, challenged with bleomycin or overexpressing a constitutively active TGF-β receptor I (TBRI CA ). Results: Twist1 mRNA and protein levels were increased in SSc skin and in murine skin of bleomycin and TBRI CA induced fibrosis. Inactivation of TBRI and Smad3/4 in vitro and in vivo demonstrated that Twist1 induction is mediated by TGFβ in a Smad dependent manner. Overexpression of Twist1 fostered pro-fibrotic effects of TGFβ on fibroblasts with increased levels of the TGFβ target genes PAI-1 and Smad7, enhanced αSMA expression, stress fiber formation and collagen release. In contrast, knockdown of Twist1 inhibited TGFβ signaling and fibroblast activation. Stimulation of fibroblasts with TGFβ induced Twist1 and E12 expression and even more pronounced expression of Id1 and Id3. Id proteins have a greater affinity for E12 competing with Twist for E12. Co-IP revealed a time-dependent shift from Twist1/E12 heterodimers to Id/E12 and Twist1/Twist1 complexes in TGFβ stimulated fibroblasts. Chip assays demonstrated that Twist1 homodimers bind to the promoters of col1a1 and col1a2. Mice lacking Twist1 selectively in fibroblasts were less sensitive to bleomycin induced fibrosis with reduced dermal thickening, myofibroblast counts and hydroxyproline content. Knockdown of Twist1 also effectively ameliorated TBRI CA induced fibrosis. Mice with ubiquitous knockout of Twist1 showed similar protection, highlighting that resident fibroblasts are the key-effector cells for the pro-fibrotic effects of Twist1 in skin fibrosis. Conclusions: We demonstrate that Twist1 amplifies the pro-fibrotic effects of TGFβ in fibroblasts. Twist1 is upregulated in SSc fibroblasts by TGFβ and in turn potentiates canonical TGFβ signaling to further stimulate fibroblast activation and collagen release. Inactivation of this positive feedback loop by targeting Twist1inhibits the pro-fibrotic effects of TGFβ and effectively reduces experimental fibrosis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2256